Outcome And Etiology of Patients Admitted with Acute Viral Hepatitis At Naimat Begum Hamdard University Hospital Karachi - Abdul Samad; Adeel Ahmed; Muhammed Rehan; Syed Saif Ali (Pakistan Journal of Medicine and Dentistry)
Background:Acute viral hepatitis is a significant public health challenge in Pakistan, particularly in urban centers like Karachi, where poor sanitation and healthcare infrastructure exacerbate its burden. This study aims to evaluate the etiology, clinical presentations, laboratory findings, and outcomes of patients admitted with acute viral hepatitis.